2022
DOI: 10.3390/technologies10020050
|View full text |Cite
|
Sign up to set email alerts
|

The NESTORE e-Coach: Designing a Multi-Domain Pathway to Well-Being in Older Age

Abstract: This article describes the coaching strategies of the NESTORE e-coach, a virtual coach for promoting healthier lifestyles in older age. The novelty of the NESTORE project is the definition of a multi-domain personalized pathway where the e-coach accompanies the user throughout different structured and non-structured coaching activities and recommendations. The article also presents the design process of the coaching strategies, carried out including older adults from four European countries and experts from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The virtual coach provides personalised tasks that could be carried out to maintain or improve the well-being in the different domains. The NESTORE platform has been co-designed with older adults from four European countries [54]. Also, this process allowed the research team to identify the need to integrate the suggested coaching activities into the existing daily routines.…”
Section: Virtual Coaches For Older Adults' Well-beingmentioning
confidence: 99%
“…The virtual coach provides personalised tasks that could be carried out to maintain or improve the well-being in the different domains. The NESTORE platform has been co-designed with older adults from four European countries [54]. Also, this process allowed the research team to identify the need to integrate the suggested coaching activities into the existing daily routines.…”
Section: Virtual Coaches For Older Adults' Well-beingmentioning
confidence: 99%
“…In the context of the Nestore project (Angelini et al, 2022), multiple interfaces were introduced to older adults, including a chatbot and a tangible vocal coach. However, the independent use of each interface led to certain information being available exclusively on one platform.…”
Section: Multimodal Interaction Frameworkmentioning
confidence: 99%
“…Furthermore, we conducted experiments with frail MCI older adults to evaluate the effectiveness of mobile and e-health services, providing valuable insights into the practical applications of such technologies in real-life scenarios [15]. These aspects have been taken into account in the design of the NESTORE e-Coach [16], a multi-domain pathway to well-being in older age. This comprehensive system integrates various aspects, including physical, cognitive, social, and nutritional dimensions, to deliver personalized coaching interventions for older adults.…”
Section: Context Awareness and Behavioral Shift Detectionmentioning
confidence: 99%